TEA5K: a high-resolution and liquid-phase multiple-SNP array for molecular breeding in tea plant - Dingding Liu; Chenyu Zhang; Yuanyuan Ye; Piao Mei; Yang Gong; Zhen Liu; Chao Sun; Xuecheng Zhao; Shiqi Ding; Jiedan Chen; Liang Chen; Chunlei Ma (Journal of Nanobiotechnology)
Abstract Background High-throughput genotyping technology has become an indispensable tool for advancing molecular breeding and genetic research in plants, facilitating large-scale exploration of genomic variation. Genotyping technology based on liquid-phase array utilizes streptavidin-coated nanomagnetic beads to capture biotin-modified probes, thereby capturing the target sequence on the genome, achieving the purpose of genotyping. This study aims to develop a novel liquid-phase for tea plant, which can be used for cultivar identification, genetic map construction, Quantitative Trait Locus (QTL) mapping of key agronomic traits in tea plants, and genetic evolution analysis. Result We developed a highly efficient multiple-SNP array, the TEA5K mSNP array, which comprises 5,781 liquid-phase probes based on the Genotyping by Target Sequencing (GBTS) system. Using this array, we genotyped 231 developed tea cultivars, revealing that genetic similarity within the same cultivar ranged from 92.53–97.95%, whereas genetic similarity between different cultivars generally remained below 82.36%. Furthermore, utilizing this array, we constructed a high-density genetic map consisting of 3,274 markers, covering a total genetic distance of 2,225.19 cM, with an average marker interval of 0.76 cM. The high-resolution genetic map facilitated the identification of multiple QTLs linked to eight amino acid components, as well as two molecular markers strongly associated with the albino-leaf trait in the ‘Huangjinya’ cultivar, both mapped to chromosome 8. Moreover, we applied the array to analyze the population structure and phylogenetic relationships of 519 tea germplasm, classifying them into three major groups: wild accessions, landraces, and modern cultivars. Notably, modern cultivars exhibited lower genetic diversity compared to landraces. Additionally, we observed substantial genetic differentiation between wild resources and modern cultivars, with minimal to no gene flow from wild populations into domesticated cultivars. These findings suggest that modern tea breeding faces an “improvement bottleneck,” a challenge similar to that encountered in other perennial crops. Conclusion The TEA5K mSNP array is presented as a flexible, cost-effective, and low-maintenance genotyping tool that significantly enhances both genetic research and molecular breeding in tea plants. By providing a robust platform for genome-wide analysis and facilitating the identification of key QTLs, this tool offers valuable insights for improving the genetic diversity and agronomic performance of tea cultivars. Graphical Abstract